2016
DOI: 10.5937/leksir1636061m
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation on efficiency of muches and other mechanical weeding methods applied in Mentha piperita L.: Cultivation

Abstract: SUMMARYPeppermint (Mentha x piperita) is a perennial, medicinal and aromatic, cultivated plant species belonging to Lamiaceae family. In this study, survey of 9 organic mulches (straw, chopped pieces of the pine bark, sawdust of acacia, cardboard, dry pine needles, chopped maize sedge, chopped pieces of the acacia bark, herbal composts 1 and 2), 1 biodegradable (black mulch film) and 4 plastic mulch films (silver-brown, perforated black, black, black "agrotextil") were tested in Mentha x piperita experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Dhima et al [ 20 ] reported that the largest losses in annual cultivated aromatic plants were caused by weeds. Matković et al [ 21 ] recorded a 88% loss of aerial biomass of peppermint to weeds, compared to non-weeded control in South Banat in Serbia. Darre et al [ 22 ], in two-year trials, revealed a yield loss of the same species of 35.7% and 50.9% in weeded, compared to non-weeded plots at a Cordoba site in Argentina.…”
Section: Introductionmentioning
confidence: 99%
“…Dhima et al [ 20 ] reported that the largest losses in annual cultivated aromatic plants were caused by weeds. Matković et al [ 21 ] recorded a 88% loss of aerial biomass of peppermint to weeds, compared to non-weeded control in South Banat in Serbia. Darre et al [ 22 ], in two-year trials, revealed a yield loss of the same species of 35.7% and 50.9% in weeded, compared to non-weeded plots at a Cordoba site in Argentina.…”
Section: Introductionmentioning
confidence: 99%